2017
DOI: 10.3892/ol.2017.5930
|View full text |Cite
|
Sign up to set email alerts
|

Transcript levels of ten-eleven translocation type 1–3 in cervical cancer and non-cancerous cervical tissues

Abstract: Abstract. Decreased expression of ten-eleven translocation (TET1, TET2 and TET3) proteins has been reported in various types of cancer. However, the expression levels of TET proteins in cervical cancer (CC) remain to be elucidated. The present study determined the levels of TET1, TET2 and TET3 transcripts in cancerous (n=80) and non-cancerous cervical tissues (n=41). The results revealed a significant reduction in TET1 transcripts (P=0.0000001) in cervical tissue samples from patients with primary CC compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Several studies revealed that high expression of TET3 was revealed in renal cell carcinoma as well as endometrial cancers, and high mRNA levels of TET3 were independent predictors of poor outcome in renal cell carcinoma patients [29,30]; whereas, several other investigations reported that TET3 was low-expressed in diverse human cancers. For instance, Bronowicka-Kłys et al showed that TET3 transcript levels were lower in stage III samples of cervical cancer [31]. Moreover, TET3 mRNA was decreased in chronic lymphocytic leukemia cells compared with healthy B cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that high expression of TET3 was revealed in renal cell carcinoma as well as endometrial cancers, and high mRNA levels of TET3 were independent predictors of poor outcome in renal cell carcinoma patients [29,30]; whereas, several other investigations reported that TET3 was low-expressed in diverse human cancers. For instance, Bronowicka-Kłys et al showed that TET3 transcript levels were lower in stage III samples of cervical cancer [31]. Moreover, TET3 mRNA was decreased in chronic lymphocytic leukemia cells compared with healthy B cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylation is removed by zinc-dependent Class I, II, and IV histone deacetylases (HDAC) or Nicotinamide adenine dinucleotide + (NAD+)-dependent sirtuins that are also referred to as Class III HDACs. HDACs remove ε-amino acetyl groups from lysine residues in histones and in non-histone proteins (especially mediated by Class II HDACs, which are also found in the cytoplasm), which explains the pleiotropic effects and rather narrow therapeutic window of HDAC inhibitors (HDACi) in humans [42,43]. HDACs are part of larger multi-enzyme complexes, including Sin3, NuRD, and Co-REST, that determine their target recognition and substrate specificity, but also have demethylase properties [44,45].…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
“…TET2 has been previously implicated in various types of malignancies ( 11 , 42 46 ). Data from the present study imply that TET2 protein expression is upregulated when exposed to a combined estrogen-progesterone treatment for 24 hours ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%